Long term effect of fluoxetine and memantine on biochemical markers of Alzheimer’s disease in scopolamine-induced mice - Istifo, N. N. H.; Al-Zobaidy, M. A. J.; Abass, K. S. (Regulatory Mechanisms in Biosystems, 2023)
Alzheimer’s disease is a chronic neurological illness that causes considerable cognitive impairment. However, there is no effective treatment for this disease. Therefore, the current study aimed at investigating the long-term effects of fluoxetine and memantine on biochemical markers of Alzheimer’s disease in scopolamine-induced mice. In this study, adult female mice were divided into four equal groups; normal control received distilled water only, the untreated Alzheimer’s disease group received scopolamine intraperitoneal IP/SCM for 14 days, following which distilled water was given for six months, the memantine-treated Alzheimer’s disease group received IP/SCM for 14 days then memantine hydrochloride for 6 months, the fluoxetine-treated Alzheimer’s disease group received IP/SCM for 14 days then fluoxetine hydrochloride for 6 months. The results show that after 2 weeks of induction the mean level of amyloid β and MDA were significantly elevated, while the mean level of BDNF and TAS were significantly reduced in comparison with the normal control group. After 3 months, both treatments (memantine and fluoxetine) caused a highly significant decrease in the mean levels of amyloid β and malondialdehyde as well as an increase in the mean levels of brain derived neurotrophic factor and total antioxidant status in Alzheimer’s disease treated mice in comparison with Alzheimer’s disease untreated mice. However, after 6 months of treatment, the effects of fluoxetine were more significant than those of memantine. In conclusion, fluoxetine has significant effects on biochemical markers of Alzheimer’s disease and these effects are time-dependent as well as more significant than those of memantine, which suggests the potential usefulness of the former in treatment of this disease.